Literature Review Tranformational Leadership - Intan Fajar Daratista; Lailatul Fitriyah; Mochammad Isa Anshori (Populer: Jurnal Penelitian Mahasiswa, 2023)
Human resource management must be carried out professionally in order to produce competent human resources to improve the performance of individuals and companies. The role of a leader is very important in improving employee performance, because effective leadership provides direction to the efforts of all workers in achieving organizational goals. One of the appropriate leadership styles in dealing with change and addressing the proactive nature of employees is a transformational leadership style that brings change through a clear vision by involving subordinates in every activity. The right leadership style will make employees respectful at work and willing to contribute their best. With the implementation of the transformation leadership style in the company, it will create maximum employee performance which will affect the company's progress.